Renewable Energy Policy Development in Thailand - Kahintapongs, Suwattana (International Journal of Multidisciplinary in Management and Tourism, 2020)
This paper is attempting to explore renewable energy policy development in Thailand. Renewable energy is mostly derived from natural resources and hence considered clean and environmentally friendly. However, there exist some hindrances to the development of renewable energy and the costs of harnessing renewable energy resources are still high compared with the costs of using commercial energy, particularly, the development of solar and wind energy which require the use of high cost technology. Renewable energy that has high potential to be used in place of fossil energy includes, for example, hydropower, biogas and biomass energy, solar energy and geothermal energy. Studies and development on these energy sources have continuously been undertaken by several agencies, both at the local level initiated by local intellect and at the government level. At present, the development of renewable/alternative energy has become a focus of interest and wider utilization has been promoted to replace conventional energy consumption in parallel with the efforts to stimulate people to use energy efficiently and economically.